2001
DOI: 10.1554/0014-3820(2001)055[2429:fsgbdo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Genetically Based Differentiation of Life-History Traits in the Perennial Shrub Lupinus Arboreus

Abstract: Across large spatial scales, plants often exhibit genetically based differentiation in traits that allow adaptation to local sites. At smaller spatial scales, sharp boundaries between edaphic conditions also can create strong gradients in selection that counteract gene flow and result in local adaptation. Few studies, however, have examined the degree to which continuous populations of perennial plants exhibit genetically based differentiation in life‐history traits over small spatial scales. We quantified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Finally, the differences in the materials analyzed (seeds for allozymes and adult plant leaves for the AFLP and ISSR analyses) may have also contributed to the discrepancies. From seeds to adults, the level of differentiation may increase, as reported for Brongniartia vazquezii Dorado (F ST : 0.0705 for seedlings and 0.1013 for adults; González-Astorga & Núñez-Farfán, 2001) and Lupinus arboreus Sims (F ST : 0.002 for seeds and 0.041 for juvenile plants; Kittelson & Maron, 2001). Such increases in differentiation may be due to natural selection, which plays a significant role during development from seedlings to adults.…”
Section: Comparison Of Different Molecular Markersmentioning
confidence: 69%
“…Finally, the differences in the materials analyzed (seeds for allozymes and adult plant leaves for the AFLP and ISSR analyses) may have also contributed to the discrepancies. From seeds to adults, the level of differentiation may increase, as reported for Brongniartia vazquezii Dorado (F ST : 0.0705 for seedlings and 0.1013 for adults; González-Astorga & Núñez-Farfán, 2001) and Lupinus arboreus Sims (F ST : 0.002 for seeds and 0.041 for juvenile plants; Kittelson & Maron, 2001). Such increases in differentiation may be due to natural selection, which plays a significant role during development from seedlings to adults.…”
Section: Comparison Of Different Molecular Markersmentioning
confidence: 69%
“…Such differentiation is somewhat surprising since other research at the same site suggested that gene flow is not restricted between these populations (Kittelson and Maron, 2001). Therefore, it seems likely that selection produced site-specific patterns in lupine traits, including alkaloids.…”
Section: Discussionmentioning
confidence: 80%
“…The selective agents responsible for producing the local differentiation that we observed remain to be identified, but may involve a combination of edaphic and biotic pressures unique to each area. Life history traits, including plant size and fecundity, also varied substantially across the Bodega Marine Reserve, among families from different origins, and among different maternal parents (Kittelson and Maron, 2001). Thus, selection may act on a suite of correlated traits that vary among populations and among parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiyear field studies, in particular, have the distinct advantage of detecting general patterns of adaptation and/or plasticity at multiple life-history stages even when there is interannual variation in conditions (Kittelson and Maron, 2001;Mojica and Kelly, 2010;Å gren and Schemske, 2012). The extent and directionality of natural selection can change through ontogeny, and selection detected at one lifehistory stage may misrepresent selection integrated across the lifetime.…”
Section: Genetic and Plastic Responses To Environmental Heterogeneitymentioning
confidence: 99%